PENGARUH INVESTASI DAN BELANJA MODAL PEMERINTAH DAERAH TERHADAP PENDAPATAN ASLI DAERAH PEMERINTAH DAERAH DAERAH ISTIMEWA YOGYAKARTA DENGAN TINGKAT KEMISKINAN SEBAGAI VARIABEL INTERVENING - Ihsan, Muhammad Fairuz (MANAJEMEN DEWANTARA, 2025)
This study aims to analyze the effect of Domestic and Foreign Investment and Regional Government Capital Expenditure on Local Own-Source Revenue in the Yogyakarta Special Region, with the Poverty Rate as an intervening variable. The research focuses on understanding how these factors influence local government revenue, considering the poverty rate's role in the relationship. This study employs a quantitative research approach using secondary data collected from 2014 to 2023. Path analysis is used to assess direct and indirect relationships among the variables. Several classical assumption tests, such as normality, multicollinearity, heteroscedasticity, and autocorrelation tests, are conducted to ensure the model's validity and reliability. The results show that Domestic and Foreign Investment and Regional Government Capital Expenditure have no significant direct effect on Local Own-Source Revenue. However, the Poverty Rate significantly mediates the relationship between these variables and Local Own-Source Revenue. This indicates that efforts to increase regional revenue should focus on poverty reduction as a strategic approach to optimizing the impact of investments and government spending. The findings provide valuable insights for policymakers in designing effective strategies to enhance regional revenue through poverty alleviation programs.